The Restless and Relentless Mind of Wes Jackson : Searching for Sustainability - Jensen, Robert 1958-; Jensen, Robert 1958- (Book collections on Project MUSE., 2021)
"In this short-form manuscript, Jensen provides readers with a core discussion of Wes Jackson's major ideas and contributions to environmental sustainability. Raised on a farm and trained as a botanist and geneticist, Jackson left a tenured job as a full professor in the mid-1970s to launch The Land Institute, which has grown to be an internationally recognized center for sustainable agriculture research. Written in close contact with Jackson, Jensen's work organizes some of Jackson's key insights from his lifelong efforts to see small and think big, and is designed as both an introduction to those ideas and a supplemental text to Jackson's own writings"